Ingresos no petroleros y su incidencia en el presupuesto general del estado ecuatoriano durante los periodo 2015-2017 - Maldonado Bermudes, Alexis Nicole (2019)
The following research work aims to know what the incidence of non-oil revenue in the General budget of the State of Ecuador during the 2015-2017. To carry out this investigation will analyze the evolution of the general del Estado (PGE) budget during the 2015-2017, whereas as a basis of analysis the period to 2014 in order to establish the variation with the consequent year……….